2020
DOI: 10.18203/2320-1770.ijrcog20204778
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid: a biochemical prognostic indicator of pregnancy outcomes among pre-eclampsia patients at the federal medical centre, Yenagoa

Abstract: Background: High levels of uric acid concentration over normal pregnant values have been reported previously in established preeclampsia, hence it was suggested to be a useful biochemical prognostic marker of the disease.Methods: This is a hospital based prospective case control study where 100 patients with preeclampsia were recruited consecutively as they were admitted. 100 non-pre-eclamptics were also recruited as control. The foetomaternal data, adverse perinatal outcomes, maternal serum uric acid levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Furthermore, our study found a significant increase in Uric acid levels in PE vs. Control. The finding was similar to those of previous studies [27,28] . The OR of UA was three times higher than control; it might be a risk factor for PE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our study found a significant increase in Uric acid levels in PE vs. Control. The finding was similar to those of previous studies [27,28] . The OR of UA was three times higher than control; it might be a risk factor for PE.…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress, hypoxic placental tissue, and endothelial dysfunction [30] may further enhance xanthine oxidase levels, thereby causing an increase in serum UA levels. Therefore, it may be used as an early prognostic indicator of the pathophysiology of PE [27] . We could not find any studies showing the association of study parameters (RTL, MDA, and CRP) with an increase in BP (10 mmHg) in PE.…”
Section: Discussionmentioning
confidence: 99%
“…The mean SUA of the preeclampsia group was much higher than the normotensive group. This finding was consistent with the study by Sultana et al, Obagah et al and Ugwuanyi et al [38][39][40] This elevated SUA in preeclamptic women supports the theory of hypoxia and ischemia of the placenta tissue that increases substrate for increased uric acid production by xanthine oxidase, coupled with a poor renal clearance of uric acid in preeclampsia.…”
Section: Discussionsupporting
confidence: 92%
“…7 Predictive factors for preeclampsia have been shown to play helpful roles in the prevention, early institution of management, and prognosis of this disorder. [17][18][19] The objective of this study was to determine the incidence, clinical characteristics, maternal and perinatal outcomes of HDP at the Federal medical centre, Yenagoa, Bayelsa State, South-South Nigeria.…”
Section: Introductionmentioning
confidence: 99%